Travmatologik kasalliklari haqida tushuncha - Raimberdiyeva Madina Solimurod qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This article analyzes in detail the diagnostic methods, types, causes, and symptoms of traumatological diseases. This article provides a general understanding of traumatological diseases. Modern medical technologies, surgical methods, and rehabilitation measures play an important role in the treatment of traumatological diseases. The article also pays special attention to preventive measures related to rheumatological diseases of trawlers.